2019
DOI: 10.3389/fneur.2018.01154
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution MRI Study of the Relationship Between Plaque Enhancement and Ischemic Stroke Events in Patients With Intracranial Atherosclerotic Stenosis

Abstract: Purpose: To investigate the relationships among the degree of intracranial atherosclerotic stenosis (ICAS), plaque enhancement (PE), and ischemic stroke events (ISEs) using 3. 0 T high-resolution magnetic resonance imaging (HR-MRI).Materials and Methods: Fifty-two ICAS patients who underwent HR-MRI were retrospectively analyzed. The patients were divided into two groups according to the results of whole-brain digital subtraction angiography (DSA): the mild-moderate stenosis group (group MID) and the severe ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…In recent years, some investigations have researched the clinical value of plaque enhancement in intracranial artery stenosis. Their results showed that the plaque enhancement identified on HRMRI could potentially serve as a marker of culprit plaques (6,13,17). Pathological studies have arrived at similar conclusions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In recent years, some investigations have researched the clinical value of plaque enhancement in intracranial artery stenosis. Their results showed that the plaque enhancement identified on HRMRI could potentially serve as a marker of culprit plaques (6,13,17). Pathological studies have arrived at similar conclusions.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies (1,14) have reported that PR is related to acute stroke. Other studies have suggested that obviously enhanced plaques are associated with recent ischemic events (13,15,16). Research has also found that patients with MCA-induced stroke recurrence have a higher plaque burden (11).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Enhancement of intracranial arteries, associated with increased neovascularization and endothelial permeability, is an important marker that has been used as a high‐risk feature of unstable plaques 33 . Wang et al showed that plaque enhancement was an independent risk factor for acute ischemic stroke events 34 . Determination of unstable, nonstenotic plaques using 3D IVWI could help appropriately direct treatment planning, for example, giving more aggressive medical treatment for patients with unstable plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the potential effect of USPION-labeled EPCs homing to injured endothelium and whether local atherosclerosis could be prevented by this EPC administration. High-resolution MRI can detect plaque components in vivo , such as intra-plaque or subintimal hemorrhage, fibrous cap and lipid-rich plaque core ( 78 80 ). Thus, using USPIONs to enhance MRI could be used to show plaque inflammation in vivo ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%